Effects of soil properties and time of exposure on gene expression of Enchytraeus albidus (Oligochaeta) - Gomes, Susana I. L.
Changes in soil properties (e.g. pH, organic matter content, granulometry) can influence chemical toxicity to organisms and act alone as stressors. Previous studies on Enchytraeus albidus showed that changes in soil properties caused effects on reproduction and avoidance behavior and also oxidative stress. In addition, results at the transcritptomic level indicated changes in gene expression profile due to soil properties changes. In this study, E. albidus was exposed to modified versions of the artificial standard OECD soil (higher clay and lower sand proportion, lower pH, and lower organic matter content) in different exposure times (2, 4 and 8 days). The gene expression profile was characterized using a class comparison statistical analysis. Results indicated that the transcriptional response was time dependent, with different genes being affected at different time points. Results also showed some genes (and biological functions) being affected in a soil specific way. The unknown gene function in the data-set makes further discrimination difficult. (C) 2011 Elsevier Ltd. All rights reserved.